Is IR Theory White? Racialised Subject-Positioning in Three Canonical Texts - Sabaratnam, Meera (Millennium, 2020)
Racism is a historically specific structure of modern global power which generates hierarchies of the human and affirms White supremacy. This has far-reaching material and epistemological consequences in the present, one of which is the production and naturalisation of White-racialised subject positions in academic discourse. This article develops a framework for analysing Whiteness through subject-positioning, synthesising insights from critical race scholarship that seek to dismantle its epistemological tendencies. This framework identifies White subject-positioning as patterned by interlocking epistemologies of immanence, ignorance, and innocence. The article then interrogates how these epistemological tendencies produce limitations and contradictions in international theory through an analysis of three seminal and canonical texts: Kenneth Waltz’s Theory of International Politics (1979), Robert Keohane’s After Hegemony (1984) and Alexander Wendt’s Social Theory of International Politics (1999). It shows that these epistemologies produce contradictions and weaknesses within the texts by systematically severing the analysis of the international system and the ‘West’ from its actual imperial conditions of possibility. The article outlines pathways for overcoming these limitations and suggests that continued inattention to the epistemological consequences of race for International Relations (IR) theory is intellectually unsustainable.